Inflammation, muscle health and aging: Calf circumference as a cost-effective diagnostic indicator of Sarcopenia - Sharon P Rose; Anju Srinivas; Akila Prashant; Prathiba Periera; Suma M Nataraj; Kusuma K Shivashankar (Archives of Gerontology and Geriatrics Plus)
Background: This study aims to investigate the levels of interleukin6(IL6), interleukin 10(IL10), the IL6:IL10 ratio, and various anthropometric measurements in different stages of sarcopenia among older individuals. Methodology: Conducted as a one-year cross-sectional study using purposive sampling, involving individuals aged 58–85 years, screened for sarcopenia based on the AWGS-2019 criteria. Case-finding methods included the SARCCalF questionnaire, handgrip strength(HGS), and chair-stand tests(CST). Anthropometric measurementswere recorded for all participants, allowing for the calculation of body mass index(BMI), waist-to-hip ratio(WHR), and appendicular skeletal muscle mass index(ASMI). Additionally, IL6 and IL10levels were estimated using Sandwich-ELISA. Results: Among the 130participants, 33 were free from sarcopenia, 35 exhibited pre-sarcopenia, 29 had sarcopenia, and 33 presented severe-sarcopenia. A majority (63 %) of the participants were male, and a substantial portion (77 %) had both diabetes and sarcopenia. The study's findings revealed that the SARCCalF questionnaire demonstrated a lower mean score in the non-sarcopenia group, with an increasing trend from pre-sarcopenia to severe-sarcopenia groups. HGS, CST results, and ASMI exhibited a reverse trend. Post-Hoc Tukey's tests revealed that IL6, IL10, IL6:IL10, and Calf Circumference(CC) exhibited significant differences between the study groups. Furthermore, ROC analysis demonstrated that IL6, IL10, IL6:IL10, and CC possessed an AUC ranging between 0.7 and 0.9, showcasing good sensitivity and specificity in distinguishing between non-sarcopenia and pre-sarcopenia. Conclusion: This study highlights the utility of IL6, IL10, IL6:IL10, and CC in the early identification of pre-sarcopenia among older individuals, offering valuable insights for clinicians to intervene promptly and enhance their quality of life.